Photorhabdus Luminescens Phase II Cells Growth Kinetic Study Using A 5L A Plus Sartorius Stedim Biostat® Fermentation System - Jesse O’Campo; Devang Upadhyay; Sivanadane Mandjiny; Rebecca Bullard-Dillard; Jeff Frederick; Leonard Holmes (European Scientific Journal, ESJ, 2017)
Photorhabdus luminescens lives symbiotically with the nematode species Heterorhabditis bacteriophora. This symbiotic couple may become a bio-control key to replacing chemical pesticides. The nematode is able to infect a wide variety of destructive insects without causing harm to beneficial insect species. There are numerous advantages of biocontrol methods including decreased maintenance and less repeated use than chemical pesticides. Nematodes are also resilient to the environment for reproduction. To better assess the growth characteristics of Heterorhabditis bacteriophora, the growth kinetics of the bacterial symbiont Photorhabdus luminescens must be understood. By varying the media composition, optimal conditions were found to present the highest specific growth rate and the shortest doubling time of P. luminescens. These conditions could be scaled into mass production with high yield.